2014
DOI: 10.1007/s13205-014-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment for hyperaccumulatory and phytoremediation capability of three wild weeds

Abstract: The composition and the organization of soil are changing rapidly by the diverged mankind activities, leading to the contamination of environment. Several methods are employed to clean up the environment from these kinds of contaminants, but most of them are costly and ineffective to yield optimum results. Phytoremediation is a natural green technology, which is eco-friendly for the removal of toxic metals from the polluted environment. Phytoremediation is a cost-effective technique through which the cleanup o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…Although there have not been any major reports on heavy metal uptake by medicinal cannabis, there have been a number of studies on the uptake of heavy metals by industrial hemp ( Cannabis sativa L .). This indicates that the cannabis plant is very efficient in the uptake of heavy metals from contaminated sites and can be considered as a potential candidate for phytoremediation of contaminated soils .…”
Section: Resultsmentioning
confidence: 99%
“…Although there have not been any major reports on heavy metal uptake by medicinal cannabis, there have been a number of studies on the uptake of heavy metals by industrial hemp ( Cannabis sativa L .). This indicates that the cannabis plant is very efficient in the uptake of heavy metals from contaminated sites and can be considered as a potential candidate for phytoremediation of contaminated soils .…”
Section: Resultsmentioning
confidence: 99%
“…Many phytoremediation studies have shown the potential of weed species to remove heavy metals from contaminated environment. Weeds such as Poa annua (for Cu, As), Tephrosia purpurea (for Mn), Cannabis sativa (for Cr), Solanum nigrum (for Mn), Dissotis rotundifolia and Kyllinga erecta (for Pb), Calotropis procera (for Zn, Mn, Cd, Cu), Withania somnifera (for Cu, Mn, As), Eclipta alba (for Cu, Mn, As), Heliotropium ellipticum (for Cu, Mn, As), and Cannabis sativa, Solanum nigrum, and Rorippa globosa (for Cd) also showed good phytoremedial potential suggesting the use of these weedy plants for remediation of heavy metal-polluted soils (Varun et al 2012;Girdhar et al 2014;Lum et al 2014).…”
Section: Uptake In a Indicummentioning
confidence: 99%
“…Although weeds are considered undesirable or troublesome plants, many weeds and their relatives, occurring on mountains and other disturbed habitats, may be useful for phytoremediation (Lum et al 2014). Many studies have shown that weed species had high accumulating abilities of heavy metals and so were used to remove heavy metals from polluted environment (Lum et al 2014;Girdhar et al 2014). Weed species such as black nightshade (Solanum nigrum), hemp (Cannabis sativa), and yellowcress (Rorippa globosa) have high endurance and accumulating ability to Cd (Ji et al 2011;Shi et al 2012;Wei and Twardowska 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thlaspi caerulescens [33], kenaf [34], sunflower [35], Cannabis sativa [36,37], Tagetes minuta L. [38], cabbage [39], Brassica juncea [40], Acacia victoriae [41], and buckwheat are superior hyperaccumulators compared to other weeds and crops, and the following plants are especially remarkable. A. victoriae was found to be capable of accumulating 3, 580 mg/kg of lead from a 1, 000 mg/L solution of lead nitrate.…”
Section: Phytoextraction Of Lead By a Hyperaccumulatormentioning
confidence: 99%